Biodentine TM or MTA ProRoot TM: the comparative analysis of application in endodontics - Z. S. Khabadze; A. V. Zoryan; V. E. Magay; A. I. Ilyushina; O. I. Magomedov; N. M. Kakabadze; M. D. Abazyan (Эндодонтия Today)
Relevance. Use of materials based on the calcium silicate (CSM) in dentistry became popular with the advent of the Mineral trioxide aggregate (MTA) in 1993 as root filler. However in the market of dental services constantly new materials appear which are convenient in use, and also have the best properties, than predecessors. Recently BiodentineTM was provided as "the first universal, biologically active and biocompatible material for replacement of the damaged dentine". Producers claim that BiodentineTM has much shorter time of a curing unlike other silicate cements, such as (MTA) and also has the best mechanical and operational properties. This review of the literature is directed to comparative assessment of physical and chemical, biological ProRoot MTA TM and Biodentine TM properties.